2021
DOI: 10.3389/fphar.2021.714483
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Underlying Mechanisms, Clinical Efficacy and Safety Between Anti-PD-1 and Anti-PD-L1 Immunotherapy: The State-of-the-Art Review and Future Perspectives

Abstract: Over the past decade, diverse PD-1/PD-L1 blockades have demonstrated significant clinical benefit in across a wide range of tumor and cancer types. With the increasing number of PD-1/PD-L1 blockades available in the market, differences between the clinical performance of each of them started to be reported. Here, we provide a comprehensive historical and biological perspective regarding the underlying mechanism and clinical performance of PD-1/PD-L1 blockades, with an emphasis on the comparisons of their clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 150 publications
0
9
0
1
Order By: Relevance
“…Previous studies have suggested superior efficacy of PD-1 inhibitors than programmed cell death ligand-1 (PD-L1) inhibitors, while the difference among different PD-1 inhibitors has not been fully elucidated [ 27 ]. Currently, only nivolumab and pembrolizumab have been approved for treating MSI-H colorectal cancer [ 28 ]. Although exploratory analyses detected no significant difference in response and PFS among different PD-1 inhibitors in this study, the heterogenous regimens may exhibit different treatment efficacy and require more investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested superior efficacy of PD-1 inhibitors than programmed cell death ligand-1 (PD-L1) inhibitors, while the difference among different PD-1 inhibitors has not been fully elucidated [ 27 ]. Currently, only nivolumab and pembrolizumab have been approved for treating MSI-H colorectal cancer [ 28 ]. Although exploratory analyses detected no significant difference in response and PFS among different PD-1 inhibitors in this study, the heterogenous regimens may exhibit different treatment efficacy and require more investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Among all types of lung cancer, non-small cell lung cancer (NSCLC) accounts for approximately 85% of all cases. In recent years, immunotherapy agents, specifically immune checkpoint inhibitors (ICIs) that target programmed death 1 (PD-1) or its ligand (PD-L1), have shown revolutionary benefits against NSCLC, among other solid tumours [ 2 ]. Between 2015 and 2016, three agents, nivolumab, pembrolizumab (anti-PD-1 antibodies) and atezolizumab (anti PD-L1 antibody), were approved for the treatment of advanced NSCLC and are now widely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that peripheral blood PD-L1 + PMN frequency could represent a novel biomarker of BRAF wild type MPs. Anti-PD-1 monoclonal antibodies, by neutralizing T cell inactivation in the TME, promote an anti-tumor response in different types of cancers, thus improving patient survival ( 32 ). However, a proportion of patients still do not respond or progress after initial therapy ( 3 ), underscoring the need to delve deeper into the immunological mechanisms responsible for this lack of response.…”
Section: Discussionmentioning
confidence: 99%